2018
DOI: 10.1093/humrep/dex380
|View full text |Cite
|
Sign up to set email alerts
|

Viable acrosome-intact human spermatozoa in the ejaculate as a marker of semen quality and fertility status

Abstract: This work was supported by grants from the Innovation Fund Denmark. M.G. and S.K. work at ChemoMetec, which produces the image cytometer used in the study, M.G. hold shares in the company. The other authors have no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 27 publications
4
21
0
Order By: Relevance
“…The most significant association was observed with motility and morphology, while the association with sperm concentration was less significant. To further integrate the semen parameters into one combined clinical relevant parameter, we used the guidelines from the World Health Organisation (WHO) on normal levels of semen quality to differentiate men into groups according to the number of sperm defects and categories of high, intermediate, and low semen quality as it has recently been done in other publications [ 24 , 27 ]. This showed that men with a poor semen quality indeed had a significantly lower fraction of GalNAc-T3-positive spermatozoa in their ejaculate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most significant association was observed with motility and morphology, while the association with sperm concentration was less significant. To further integrate the semen parameters into one combined clinical relevant parameter, we used the guidelines from the World Health Organisation (WHO) on normal levels of semen quality to differentiate men into groups according to the number of sperm defects and categories of high, intermediate, and low semen quality as it has recently been done in other publications [ 24 , 27 ]. This showed that men with a poor semen quality indeed had a significantly lower fraction of GalNAc-T3-positive spermatozoa in their ejaculate.…”
Section: Discussionmentioning
confidence: 99%
“…Semen samples were collected from 206 men representing a broad spectrum of semen quality as described before [ 27 ]. Samples originated from an unselected and random sub-sample of men from infertile couples ( N = 125), men from an ongoing study of reproductive health in the general Danish population ( N = 68), and fertile men ( N = 13) who previously fathered a child.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, assays to investigate the functionality of the acrosome involve quite laborious manual procedures, and they have not been used in the clinic or in larger clinical studies. Recently, we have developed an assay based on image cytometry, which allows automatization and easy determination of the percentage of viable acrosome-intact spermatozoa in an ejaculate, an indicator of the acrosomal status [15,16]. This assay exploits the advantage of PSA coupled to fluorescein isothiocyanate (FITC) to flow via membrane pores into the acrosomal compartment of reacting acrosomes and to stabilize the acrosomal matrix allowing easy detection of spermatozoa undergoing the acrosome reaction [17].…”
Section: Introductionmentioning
confidence: 99%